41 Parliamentary Debates from the Year 1803 to the Present Time 1649 - (:unkn) unknown (My University, 1820)
"Any pike, pike head or spear in the possession of any person or in any house or place?" was subject to confiscation. Yet "any dirk, dagger, pistol or gun or other weapon" was to be seized if it was for "any purpose dangerous to the public peace?."
Keywords: PROHIBITED WEAPONS